Mitigation of oxidative stress and inflammatory factors, along with the antibrowning and antimicrobial effects of cassia seed microbial fermentation solution - Xie, Haohui; Gu, Quliang; Chen, Weiji; Meng, Xiangyu; Guo, Zhenyu; Zhang, Yue; Li, He (Frontiers in Microbiology, 2024)
Introduction Cassia seeds, originating from the mature seeds of leguminous cassia species, possess pharmacological effects attributed to their rich composition of various active ingredients, notably anthraquinones. While current research predominantly focuses on pharmaceutical extractions, there has been limited progress in fermentation studies. Methods Our study aimed to enhance the content of active compounds such as anthraquinones, flavonoids, and polyphenols using microbial fermentation techniques. We specifically optimized a fermentation system through a single-factor experimental design. Results The antioxidant properties of the fermentation solution were validated through assays involving HaCaT cells and zebrafish. We observed effective suppression of inflammatory reactions in both RAW264.7 cells and transgenic zebrafish by the fermentation solution. Moreover, significant inhibition of tyrosinase activity and melanin production was evident in B16-F10 cells and zebrafish. Positive outcomes were also obtained in antibacterial assays and chick embryo experiments. Discussion These findings highlight the potential of cassia seed fermentation solution as a safe and eco-friendly material in food chemistry and biomedical sciences.